IMPLEMENTASI MODEL PEMBELAJARAN ICARE (INTRODUCTION-CONNECT-APPLY-REFLECT-EXTEND) TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Mahdian Mahdian; Almubarak Almubarak; Nurul Hikmah (Postgraduate, University of Mataram, 2019)
This research was about the implementation of the ICARE (Introduction-Connect-Apply-Reflect-Extend) learning model to the science process skills compared to the DI (Direct Instruction) learning model. This research was a quasi-experimental design with nonequivalent control group design. The population was all students of class X MIPA SMAN 4 Banjarmasin with sample consist of 2 classes selected by cluster random sampling, X MIPA 2 as an experimental class and X MIPA 4 as a control class. Data collection techniques were used test (instruments test description question) and observation technique like using the science process skills instrument. Data analysis using t-test obtained tcount larger than ttable at the 0.05 level of significance, ie 5.9 > 2.0, it means that there were a differenct in science process skills aspect between students who had learned with the ICARE learning model and the DI learning model. Students’ science process skills enhancement in the experimental class have a gain value of 0.61 in the medium category and in the control class have a gain value of 0.40 in the medium categoryKeywords: ICARE, science process skill, electrolyte and non electrolyte solution